2001
DOI: 10.1038/84659
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 acts at the locus of the antigen-presenting dendritic cell to counter-regulate cytotoxic CD8+ T-cell responses

Abstract: The mechanism underlying suppression of immune responses by interleukin-4 (IL-4) has remained unexplained. Here we show that the antigen-presenting dendritic cell is central to counter-regulation of autoimmune disease by IL-4. IL-4 acts at the locus of the dendritic cell to decrease the cytolytic T-cell response, preventing autoimmunity. Stimulation of cytotoxic precursors by antigen pulsed dendritic cells induces their differentiation but the process is blocked by IL-4. IL-4-influenced DC produce distinct eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 46 publications
7
55
0
Order By: Relevance
“…Consistent with our findings, a number of other groups have reported that IL-4 DC generate a stronger cytolytic response compared to DC generated with GM-CSF alone [18,35,36]. Despite this difference, our data and the data from King et al [20] show that IL-4 exerts immunoregulatory effects by preconditioning the DC to alter their composition of costimulatory molecules [20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our findings, a number of other groups have reported that IL-4 DC generate a stronger cytolytic response compared to DC generated with GM-CSF alone [18,35,36]. Despite this difference, our data and the data from King et al [20] show that IL-4 exerts immunoregulatory effects by preconditioning the DC to alter their composition of costimulatory molecules [20].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that IL-4 promoted the acquisition of cytolytic capacity in the T cells. King et al [20] found the opposite. It is possible that in vivo, IL-4 would affect also other cells than DC that might reduce the cytotoxic potential.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several mechanisms of action have been suggested in the past [6,7,35] for the effect of DC and/or IL-4 in NOD mice. We opted for a different approach, using microarray analysis, to get a broader picture of the impact of DC/IL-4 treatment on gene expression in targeted tissues.…”
Section: Dc/il-4 Treatment Normalizes Gene Expression In the Plnmentioning
confidence: 99%
“…IL-4 may be important in the maintenance of a protective Th2 response [5], but it has also been implicated in the stimulation of a broader T cell repertoire composed of non-pathogenic cells [6] and in differential expression of B7.1 and B7.2 molecules by DCs, affecting the quality of CTL responses [7]. Systemic administration of IL-4 appeared to alleviate a form of unresponsiveness among NOD thymocytes and peripheral T cells, which correlated with disease protection [8].…”
Section: Introductionmentioning
confidence: 99%